Assessment of Aerodynamic Plates Subjected to Von Kármán Vortex Street for Enhancing the Wind Energy Generation in Blade-Less Devices (2023)
This study explores the feasibility of using an oscillating plate downstream of a cylindrical body to produce mechanical energy from a Von Kármán vortex street under sub-critical flow conditions (Re = 72,500). The study aims to quantify the impact of the plate length, its separation from the cylinder, and a machine damping factor on the power coefficient and the blade’s displacement to identify the optimal configuration. This preliminary assessment assumes that the plate oscillation is small enough to avoid changes in the vortex dynamics. This assumption allows the construction of a surrogate model using Computational Fluid Dynamics (CFD) to evaluate the effect of plate length and separation from the cylinder on the fluctuating lift forces over the plate. Later, the surrogate model, combined with varying machine damping factors, facilitates the description of the device’s dynamics through the numerical integration of an angular momentum equation. The results showed that a plate with a length of 0.52D, a separation of 5.548D from the cylinder, and a damping factor of 0.013 achieved a power coefficient of 0.147 and a perpendicular displacement of 0.226D. These results demonstrate a substantial improvement in the performance of blade-less generators.